Cytogenetic study of forage grasses and legumes - Mariani A.; Roscini C.; Basili F.; Paoletti R.; Rosafio M.C. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
A cytotaxonomic and cytogenetic characterization was conducted on forage legumes and grasses, such as Lotus corniculatus, Lotus alpinus, Trifolium alpinum, Phleum alpinum, Phleum pratense, Festuca rubra and Festuca pratensis collected at different altitudes in the Italian Alps, with the purpose of analysing the germplasm structure and identifying those species most suitable for establishing new improved varieties. Ploidy level, chromosome morphology, somatic karyotype and chromosome behaviour at meiosis were determined in different accessions of each species. For a better characterization of the Lotus spp. FISH was also used. Cytological analysis detected atypical chromosome numbers in some species, as well as variable chromosome numbers among individuals of the same accession in other species. Furthermore some of the species displayed variable numbers of supernumerary B-chromosomes. The origin and significance of those peculiarities in the chromosome sets are discussed and evaluated with a view to utilising the species analysed in breeding programmes.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)